2013
DOI: 10.1002/btpr.1716
|View full text |Cite
|
Sign up to set email alerts
|

Use of perfluorocarbons to enhance the performance of perfused three‐dimensional hepatic cultures

Abstract: Bioartificial liver devices (BALs) are extracorporeal systems designed to temporarily bridge patients until a suitable donated liver is available for transplantation and also have value for pharmaceutical testing applications. Yet critical issues exist that limit the functional performance of their current designs. One of these concerns scale up issues connected to oxygen (O2 ) delivery to the cells housed within their three-dimensional (3D) configurations, and its consequences to device performance. As primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Other studies using similar bioreactor setups have also found that supplementing culture medium with PFC emulsions improved cell viability, differentiation, and function for tracheal and hepatic tissue constructs. 46,47 However, one of these studies found that adding PFC emulsions to their bioreactor setup decreased chondrogenesis in the cartilaginous layer of tracheal constructs. Thus, supplementing culture medium with PFC emulsions may only benefit specific cell types.…”
Section: Current Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using similar bioreactor setups have also found that supplementing culture medium with PFC emulsions improved cell viability, differentiation, and function for tracheal and hepatic tissue constructs. 46,47 However, one of these studies found that adding PFC emulsions to their bioreactor setup decreased chondrogenesis in the cartilaginous layer of tracheal constructs. Thus, supplementing culture medium with PFC emulsions may only benefit specific cell types.…”
Section: Current Technologiesmentioning
confidence: 99%
“…Incorporation of solid peroxides in synthetic scaffolds for dermal, pancreatic, skeletal muscle, and general TE applications 4247 …”
Section: Figurementioning
confidence: 99%
“…Perfluorocarbon (PFC), a fluorine-substituted derivative of hydrocarbons, can dissolve large respiratory and other non-polar gases as compared to water [26], exhibiting a great potential for use as an oxygen transporter. PFCs have been widely used in medical applications to deliver oxygen to mammalian tissues and/or remove metabolically waste as so-called blood substitutes [27,28]. Additionally, using PFCs as oxygen carriers to enhance the efficiency of microbial, plant or animal cell growth has also been extensively reported in the past two decades [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used successfully in bioartificial liver bioreactors to meet hepatocyte oxygen demands and preserve differentiated phenotypes (Nieuwoudt et al, 2005;Kinasiewicz et al, 2008;Nieuwoudt et al, 2009). Unfortunately, common oxygen carriers in vivo and in vitro are emulsified perfluorocarbons (PFC) that, as emulsions, require excessive equipment in order to charge them with oxygen (Shi and Coger, 2013), and are thus not readily amenable to multi-well plate based cell culture and drug testing methodologies.…”
Section: Introductionmentioning
confidence: 99%